Investigation of the role of strontium on bone physiology: from a molecular biology perspective to applicability - Silva, Larwsk Hayann Gonçalves da (2023)
The development of biocompatible materials able to trigger specific cellular responses at the molecular level is the focus of tissue engineering. This challenging task involves the activation of specific molecular pathways by bioactive compounds added to the composition of biomaterials to enhance the biological response. In the special case of bone tissue, nanoparticles composed of hydroxyapatite (HA) have proven to be an excellent alternative to activate osteoblasts, the cells responsible for the formation of the bone extracellular matrix. This effect is assigned to the similarities between the mineral portion of the bone and the composition of HA. Calcium ions can be replaced by other divalent cation in the structure of HA. Among them, the substitution by strontium has been studied due to the ability of these ions to regulate the activity of osteoclasts, cells responsible for bone resorption. For instance, strontium ranelate was used in the past to treat osteoporosis. However, the need of using high doses of the compound in order to have pharmacological responses was also cause of pathological mineralization and the use of the drug was discontinued. Since then, other compounds able to control osteoblasts and osteoclasts activity using low strontium concentration have been focus of attention. However, the action of strontium upon mineralization competent cells at a molecular is still not fully understood. In this thesis, we synthesized a class of special nanoparticles enriched with strontium. The nanoparticles mimic the structure and composition of biological apatite, the mineral portion of the bone. We divided the text into two fundamental parts. First, we sought to understand whether the nanoparticles containing strontium would be capable of modulating osteocompetent cells in vitro. Hence, we investigated their role in promoting biomineralization. We synthesized apatite containing different percentage of calcium replacement by strontium: (1) hydroxyapatite-based nanoparticles in the absence of strontium, named NanoSr 0%, (2) HAp-based NanoSr 10%, where 10% of calcium was replaced by strontium, and (3) HAp-based NanoSr 90%. We observed that NanoSr 90% was the most effective nanoparticle in inducing mineral deposition in the extracellular matrix by osteoblasts. Moreover, NanoSr 90% upregulated markers of osteoblast differentiation and maturation, as well as was linked to high alkaline phosphatase activity. After that, we studied the NPs´ effect on osteoclast survival and differentiation. We observed that all the NPs had the ability to inhibit osteoclast differentiation without affecting their viability. Afterward, we analyzed whether NanoSr 90% associated with a worldwide used porous polymethylmethacrylate cement (pPMMA) would effectively bring benefits to the biomaterial as an agent of strontium delivery in vivo using rabbits as animal models. We noticed that NanoSr90% modulated OCN and BMP2 gene expression levels, which are markers of osteoblast turnover. Additionally, we observed osteoblast migration towards the pPMMA cement area, as well as collagen type I deposition, which are indicative of bone formation. These outcomes advocate that NanoSr 90% is a strong candidate to be further tested as an active biomaterial. In the second part of the thesis, we focused on understanding how strontium regulates biomineralization at the molecular level. Here, we opted to use strontium ranelate as the main source of strontium instead of the nanoparticles due to the following reason, the cell line chosen for this characterization (odontoblast, 17IIA11) is already committed to a mineralizing phenotype, hence they do not require a differentiation step. For this reason, the extracellular matrix (ECM) full mineralization occurs in approximately 6 days. The NPs requires at least 14 days to have its maximum delivery of strontium into the media, which is not viable to be tested for this cell line. Additionally, as a comparison, we also studied the effect of Ca2+ in the form of CaCl2 and inorganic phosphate (Pi), which are the two most well-known ions involved with bone physiology. Herein, we hypothesized that strontium affects mineralization on two different levels, (1) by regulating osteogenic markers and cell commitment, and (2) by regulating the secretion and function of matrix vesicles (MVs). The results revealed that Sr2+ regulated Erk1/2 and CREB signaling pathways, as well as modulated osteogenic-related genes. The effect of Sr2+ on osteocompetent cells is dose-dependent, which means that high doses of Sr2+ abolished mineralization, while low doses promoted it. Further, we treated the cells with the ions and isolated the matrix vesicles trapped in the extracellular matrix. A curious and yet not fully understood behavior was perceived. Here, we found that strontium diminished MVs\' release, but enhanced their ability to mineralize the ECM. The morphology of the vesicles was characterized by atomic force (AFM) and transmission electron (TEM) microscopy. The results revealed changes in the viscoelastic properties of MVs derived from cells treated with Pi, CaCl2, and strontium. Finally, we determined the MV´s lipid content using lipidomic analysis, which showed that the lipid composition entirely changes depending on the treatment. MVs derived from cells stimulated with strontium were enriched in ceramide (Cer) and sphingomyelin (SM) lipids, which are required for MV turnover. In conclusion, the findings presented in this thesis attested for the potential use of strontium-based nanoparticles for bone repair. Additionally, this thesis added one more brick to the overall and ever-growing knowledge regarding the strontium basic mechanisms of action on osteocompetent cells. Finally, for the first time in the literature we have demonstrated that strontium affects the MVs lipid content profile, which in turn increased the matrix vesicle function.